Hysterectomy after uterus transplantation and detailed analyses of graft failures - Camilla C. Karlsson; Pernilla Dahm‐Kähler; Niclas Kvarnström; Johan Mölne; Verena Broecker; Mats Brännström (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction The first live birth after uterus transplantation occurred in Sweden in 2014. Uterus transplantation has repeatedly, and at many centers worldwide, proven to be a feasible treatment for absolute uterine factor infertility. Hysterectomy in live donors and transplantation are well described in numerous reports. However, there are no reports of hysterectomy in the recipient after uterus transplantation, which will occur at either graft failure, after childbirth, or after numerous failed pregnancy attempts. We present the first report of hysterectomy in recipients after uterus transplantation with detailed analyses of findings in conjunction with graft failures. Material and Methods An analysis of recipient hysterectomies (n = 10), performed in 2012–2020, was conducted. Data from the international uterus transplantation registry (ISUTx registry) were extracted, and medical records were systematically reviewed, to collect and compile characteristics of recipients and donors, as well as pre‐, per‐, and postoperative data, including clinical course of graft failures. Results Hysterectomy in recipients was performed in conjunction with cesarean section (n = 3), 3–6 months after cesarean section (n = 3), or after failed pregnancy attempts (n = 1) or graft failure (n = 3). The durations of anesthesia (2 h 36 min to 7 h 35 min) and hysterectomy surgery (1 h 42 min to 5 h 52 min) ranged widely, with long perioperative interruptions for insertion of ureteral catheters in two cases. Adhesions to the uterus were abundant, the majority being mild. Three uteri that subsequently showed graft failure (hysterectomy at 1, 3, and 8 months post transplantation) showed histological signs of ischemia in biopsies taken 1‐week post‐transplant and early signs of central hypoperfusion by Doppler ultrasound. In these graft failure explants, there were no epithelial linings in the uterine cavity or in the cervix. The inner uterine wall was severely ischemic and/or necrotic, whereas outer parts were partly viable. There were signs of moderate atherosclerosis of uterine arteries but no rejection. Mild postoperative complications were frequent (6/10), with one supravaginal hematoma requiring surgical drainage. Conclusions Hysterectomy after uterus transplantation is a complex and time‐consuming procedure, and perioperative ureteral catheters may be helpful. Histopathology of early cervical biopsies showing ischemic signs may indicate subsequent irreversible damage, leading to graft failure.